Detection of Methicillin-Resistant Staphylococcus aureus Infections Using Molecular Methods - Fred C. Tenover; Isabella A. Tickler (Antibiotics, 2022)
The application of molecular detection methods for bacterial pathogens has dramatically improved the outcomes of septic patients, including those with methicillin-resistant Staphylococcus aureus (MRSA) infections. Molecular methods can be applied to a variety of clinical specimens including nasal swabs, growth in blood culture bottles, and wounds. While data show that the overall accuracy of molecular tests for MRSA is high, results can be confounded by the presence of multiple staphylococcal species in a specimen, insertions and deletions of DNA in and around the Staphylococcal Cassette Chromosome mec (SCCmec) element, and point mutations in mecA. Herein, we explore the complexities of molecular approaches to MRSA detection and the instances where phenotypic methods should be pursued to resolve discrepancies between genotypic and phenotypic results.